Of histories, erasures and the beloved: Glimpses into Philippine contemporary poetry - Roma, Dinah T. (Animo Repository, 2015)
To attempt a definition of Philippine contemporary poetry is to confront its historical and literary legacies and upheavals. While it has already been said that the Philippine writing in English is one of the most expansive in Southeast Asia, this assessment remains but a strand in the country's remarkably diverse literary milieu. There is much to be explored in the writings in Filipino; however the term may be contentious in embodying the regional languages that many of the country's writers are now advocating so as to affirm national identity. At the same time, the American literary landscape continues to dominate the poetics of many young writers as they destabilise long held creative practices. This essay does not aim to map a cross-section of today's poetic production. What it offers are glimpses of the bursting energies that propel the writings among contemporary poets. Charlie Veric Samuya's Histories (2015), Mesandel Arguelles's Pesoa (2014), and Genevieve Asenjo's bilingual collection Sa Gihapon, Palangga, An Uran (2014) are recent releases in English, Filipino, and Kinaray-a. The three languages give a sampling of the richness of Philippine literature in general. As individual works that mark various points in the three writers' career, they impress by the strategies through which they execute their poetic projects. What this essay further offers is a sense of the other voices out there simply waiting to be heard.